Analysis of discharge documentation for older adults living with dementia: A cohort study. Issue 23 (9th June 2021) - Parker, Kirsten J.; Phillips, Jane L.; Luckett, Tim; Agar, Meera; Ferguson, Caleb; Hickman, Louise D.
Abstract: Background: Older adults living with dementia frequently transition between healthcare settings. Care transitions increase vulnerability and risk of iatrogenic harm. Aim and objective: To examine the quality of transitional care arrangements within discharge documentation for older people living with dementia. Design: Secondary analysis of cohort study data. Method: A secondary analysis of the IDEAL Study [ACTRN12612001164886] discharge documents, following the STROBE guidelines. Participants had a confirmed diagnosis of dementia and were discharged from hospital to a nursing home. An audit tool was used to extract the data. This was developed through a synthesis of existing tools and finalised by an expert panel. The analysis assessed the quality of discharge documentation, in the context of transitional care needs, and presented results using descriptive statistics. Functional ability; physical health; cognition and mental health; medications; and socio environmental factors were assessed. Results: Sixty participants were included in analyses, and half were male (52%), with a total participant mean age of 83 (SD 8.7) years. There was wide variability in the quality of core discharge information, ranging from excellent (37%), adequate (43%) to poor (20%). A sub‐group of these core discharge documentation elements that detailed the participants transitional care needs were rated as follows: excellent (17%), adequate (46%) and poor (37%). Conclusion: Discharge documentation fails to meet needs of people living with dementia. Improving the quality of discharge documentation for people living with dementia transitioning from hospital to nursing home is critical to provide safe and quality care. Relevance to clinical practice: There is a need for safe, timely, accurate and comprehensive discharge information to ensure the safety of people living with dementia and prevent adverse harm.